Ser professor-pesquisador: cientistas sociais e produtivismo acadêmico nas universidades estaduais paulistas - Moraes, Lívia Bocalon Pires de (2024)
The research is part of studies on academic productivism and its repercussions on the work of professor-researchers in graduate programs in Sociology and Social Sciences at state universities in São Paulo. It focuses on the following research question: What is the influence of unequal conditions in addressing the pressures for productivist academic practices on the meanings attributed by professor-researchers to their work and the strategies they adopt in their academic-scientific practices? The objective of the investigation is to analyze the relationship between the inequality of conditions in addressing the pressures for productivist academic practices, the meanings attributed to their work by these professor-researchers, and the strategies they adopt in their academic-scientific practices. The study is grounded in Pierre Bourdieu's theory, particularly his concepts of field, capital, habitus, symbolic power, strategy, and illusio, treating professor-researchers as competing agents who occupy unequal positions within the structure of the academic field, of which graduate studies are a part. This is a mixed-methods study based on curriculum data from 145 professor-researchers affiliated with graduate programs in Sociology and Social Sciences at the University of São Paulo (USP), the University of Campinas (UNICAMP), and São Paulo State University “Júlio de Mesquita Filho” (UNESP), in the Marília and Araraquara campuses, in 2019. The methodological procedures adopted included: a literature review; document analysis of the regulations governing graduate studies and research in Brazil; statistical analysis of the Lattes curriculum vitae of the professor-researchers using Multiple Correspondence Analysis (MCA); and semi-structured interviews with eleven professors from the aforementioned graduate programs, selected based on groups resulting from the statistical analysis. The research results show that the classifications and hierarchies generated and enacted through CAPES' evaluation of graduate studies significantly affect the academic-scientific practices and shared conceptions of professor-researchers operating in the academic field. These professors recognize the institutional legitimacy of these principles as criteria for the distribution of material resources and confer upon these classifications (which become principles of vision and division) a belief in their validity as guiding precepts of intellectual work. Thus, the subjective internalization of the objective divisions established by CAPES reinforces the power of this evaluation body and the hierarchies it establishes, directly affecting the "scientific work" of professor-researchers in the Brazilian academic field. This suggests a tendency for this evaluative framework to increasingly influence the meanings that professor-researchers subjected to the "CAPES Evaluation Model" attribute to their work.